Monkeypox virus H3L protein as the target antigen for developing neutralizing antibody and serological assay - I-Hsiang Huang; Guan-Chun Lai; Tai-Ling Chao; Wang-Da Liu; Sui-Yuan Chang; Shih-Chung Chang (Applied Microbiology and Biotechnology)
Abstract The large number of atypical monkeypox (Mpox) cases caused by emerging monkeypox virus (MPXV) strains was recently found in countries and regions where the Mpox was not reported before. Diagnostic tools and therapeutic agents are important countermeasures for preventing Mpox outbreak. H3L protein is the important surface antigen of MPXV for binding to host cell receptors and mediating viral infection. A broad range of murine anti-MPXV H3L monoclonal antibodies (mAbs) recognizing various binding epitopes have been generated in the study. The rapid test composed of the mAbs 4-2A and 3-3F can specifically detect H3L protein and MPXV virion. The mAb 3-3F exhibited strong MPXV neutralizing activity in a complement-dependent manner. Notably, 3-3F binds to a unique epitope within residues 35–89 of H3L protein. The serum samples collected from Mpox patients barely bound to the N-terminal portion of H3L protein ranging from 2 to 89 residues, indicating that the content of the 3-3F-like antibody is very low in Mpox patient sera. In contrast, the seropositivity was mostly observed using the C-terminal portion of H3L protein ranging from 185 to 282 residues as the target antigen in the immunoblot analysis. Taken together, the anti-MPXV H3L mAb can be developed as the Mpox diagnostic and therapeutic agents. Furthermore, H3L protein is the promising biomarker for serological analysis. Key Points •Anti-H3L mAbs can cross-react with H3L proteins in MPXV and VACV virions. •The LFIA rapid test using the mAbs 4-2A and 3-3F can specifically detect MPXV. •MPXV was neutralized by mAb 3-3F in a complement-dependent manner